2005
DOI: 10.1111/j.1742-4658.2005.04990.x
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan tryptophylquinone cofactor biogenesis in the aromatic amine dehydrogenase of Alcaligenes faecalis

Abstract: Aromatic amine dehydrogenase (AADH) is a tryptophan tryptophylquinone (TTQ)-dependent quinoprotein that catalyses the oxidative deamination of a wide range of amines to their corresponding aldehydes and ammonia [1]. Electrons released upon substrate oxidation are transferred to the TTQ cofactor ( Fig. 1) and then to the physiological electron acceptor, azurin, which mediates electron transfer from the dehydro- The heterologous expression of tryptophan trytophylquinone (TTQ)-dependent aromatic amine dehydrogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…TTQ reduction is ϳ80 times more rapid with tryptamine and the KIE value (ϳ55) is substantially inflated compared with the KIE (ϳ12) measured with phenylethylamine (8,14,23). The conformation of intermediate IIIa with tryptamine is distinct …”
Section: Qm/mm Simulations Of the Aadh/r-phenylaminoethanol Iminium Cmentioning
confidence: 88%
See 4 more Smart Citations
“…TTQ reduction is ϳ80 times more rapid with tryptamine and the KIE value (ϳ55) is substantially inflated compared with the KIE (ϳ12) measured with phenylethylamine (8,14,23). The conformation of intermediate IIIa with tryptamine is distinct …”
Section: Qm/mm Simulations Of the Aadh/r-phenylaminoethanol Iminium Cmentioning
confidence: 88%
“…We have been able to reject the first mechanism by carefully measuring the number of electrons released per amine substrate molecule under standard assay conditions (two in all cases tested, data not shown) and by the fact that amide formation and hydrolysis are exceedingly slow (see below). Consequently, amide formation and hydrolysis cannot be an integral part of the steady-state mechanism for reaction with amines (14,23). We have demonstrated that soaking oxidized crystals of AADH with phenylacetaldehyde and ammonia for prolonged periods leads to AADH reduction.…”
Section: Reaction With Carbinolamines Leads To Formation Of Amide-ttqmentioning
confidence: 92%
See 3 more Smart Citations